A possible way to relate the covariantization and the negative dimensional integration method in the light-cone gauge - Suzuki, A. T.; Bentin, R. (World Scientific Publ Co Pte Ltd, 2001)
Here we present a possible way to relate the method of covariantizing the gauge-dependent pole and the negative dimensional integration method for computing Feynman integrals pertinent to the light-cone gauge fields. Both techniques are applicable to the algebraic light-cone gauge and dispense with prescriptions to treat the characteristic poles.
Keywords: covariantization; negative dimensional integration; noncovariant gauge theories